High strain rate properties of magnesium alloy and its nano-composites at elevated temperature using compressive split hopkinson pressure bar - Lok, Clement Jia Sheng (2015)
Magnesium alloys present itself as a highly viable replacement to aluminium and steels as structural metals, due to its high strength-to-weight ratio. This property is highly favourable in the aviation and automotive industries, which have the constant demand for lightweight materials. In this project, AZ31B and its reinforced counterparts, AZ31B/0.5%SiC and AZ31B/1.0%SiC are the materials investigated. This project has two main objectives. Firstly, the compressive properties of AZ31B and its reinforced counterparts at 100°C were investigated. Secondly, the change in compressive properties of AZ31B/0.5%SiC due to change in test temperature. All compressive tests were conducted at 3300±300/s using the Split Hopkinson Pressure Bar. It was observed that the increase in silicon carbide content improved the compressive strength, strain hardening effect as well as the energy absorption capability, without compromising the ductility of the material. In contrast, the increase in testing temperature resulted in drop in the same properties, except for the ductility, which has an opposing trend.